2001
DOI: 10.1002/1521-3765(20011015)7:20<4343::aid-chem4343>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Thermodynamic Studies of Oligonucleotides Containing the Two Isomers of Thymine Glycol

Abstract: Thymine glycol is a major type of base damage, which is formed in DNA by reactive oxygen species. I describe the synthesis of oligonucleotides containing the 5S isomer of thymine glycol, which was not obtained by the oxidation of the oligonucleotides. Before the 5S isomer was synthesized, a building block without the protection of the tertiary hydroxy function at the C5 position of thymine glycol was tested by the use of the previously reported 5R isomer. In the presence of imidazole, migration of the silyl gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 58 publications
7
65
0
Order By: Relevance
“…In this study, Tg was generated by direct oxidation of the single thymine in the template DNA using osmium tetroxide. This procedure generates 85% of the 5R isomer (28), suggesting that the reduced rate of incorporation of dAMP opposite Tg observed in our experiments was mainly due to the effect of this isomer. In support of this conclusion, kinetic analyses performed by Hanaoka and co-workers revealed that Pol ␣ incorporates dAMP opposite 5R-Tg about 16-fold less efficiently than on an undamaged template (14).…”
Section: Fig 3 Effect Of Thymine Glycol On Removal Of the Drp Residmentioning
confidence: 48%
“…In this study, Tg was generated by direct oxidation of the single thymine in the template DNA using osmium tetroxide. This procedure generates 85% of the 5R isomer (28), suggesting that the reduced rate of incorporation of dAMP opposite Tg observed in our experiments was mainly due to the effect of this isomer. In support of this conclusion, kinetic analyses performed by Hanaoka and co-workers revealed that Pol ␣ incorporates dAMP opposite 5R-Tg about 16-fold less efficiently than on an undamaged template (14).…”
Section: Fig 3 Effect Of Thymine Glycol On Removal Of the Drp Residmentioning
confidence: 48%
“…50 and 51) particularly when canonical hydrogen bonding and/or stacking interactions are absent. Such a mechanism has been implied for AP sites and thymine glycol on the basis of the lack of apparent correlations between the preference of insertion or proofreading excision of nucleotides and the T m of oligonucleotides containing these lesions (52,53). The mechanism involving steric exclusion also seems consistent with the observation that Endo III recognizes mFapyG paired with purines more efficiently than that paired with pyrimidines (activity with respect to the paired base: A Ϸ G Ͼ T Ͼ C) (22).…”
Section: Figmentioning
confidence: 64%
“…Tg lesions are a strong block to many DNA polymerases in vitro and in vivo (34). Neither isomer of thymine glycol can form a stable base pair with any nucleobase on the complementary strand (35), and DNA synthesis terminates after insertion of A opposite Tg. For example, in our experiments, DNA synthesis by the B-family DNA polymerase from RB69 (gp43) was blocked by either Tg isomer.…”
Section: Discussionmentioning
confidence: 99%